Adsorption of alizarin, Eriochrome blue black R, and fluorescein using different iron oxides as adsorbents - Pirillo, Silvina (2007)
This work presents kinetic and thermodynamic analysis of the adsorption of three dyes: alizarin, eriochrome blue black R, and fluorescein onto goethite, Co-goethite, and magnetite of medium Brunauer-Emmett-Teller surface area. The adsorption of the dyes on the oxides is fast. Fluorescein exhibits the lowest level adsorption for all adsorbents with goethite being the most efficient adsorbent when milligrams of dye per gram of oxide are considered. The Langmuir isotherm is the most appropriate for describing the adsorption data for the following systems: alizarin-magnetite and eriochrome and fluorescein with the three adsorbents, while alizarin-goethite and alizarin-Co-goethite show better fits with Freundlich isotherm. Molecular modeling using MM2 was used to analyze the steric effects on adsorption.